Consumer Perceptions, Concerns, and Purchasing Practices of Rabbit Meat in Hungary. Issue 6 (17th August 2016) - Szendrő, Katalin
ABSTRACT: Nationwide consumer research was conducted in 2014 on consumer perceptions, purchasing practices, and consumption of rabbit meat. The questionnaire revealed that respondents basically found rabbit meat healthy; however, better knowledge of positive physiological effects would lead to increased consumption. Transforming public awareness may also include the criticism of housing systems suspected to be "humanitarian." The experiment-proven conditions, in which—in contrast to human empathy and preconceptions—rabbits indeed feed well and are "happy, " should be presented to the public.